Analiza i praktyczne ujęcie metodologii i mechanizmu dokonywania waloryzacji na przykładzie ustalonego i niewypłaconego odszkodowania za wywłaszczoną nieruchomość - Antkowiak, Barbara (Studia Prawa Publicznego, 2019)
The aim of this article was to create a compilation that would allow for the inclusion in one place of universal principles necessary for the proper implementation of valorisation of the established and unpaid compensation for the expropriated property. In recent years, there has been a worrying phenomenon of arbitrariness and inconsistency in addressing the issue of the compensation valorisation mechanism in question, which is associated with the inadequate practical and mathematical implementation of the valorisation in question by public administration bodies. This may be due not so much to a lack of understanding of the subject as to insufficient practical knowledge of how to make mathematical calculations correctly. It should be remembered that an incorrect adjustment affects the final result, which is the amount of compensation. Thus, this error may imply undue payment of compensation, both on the part of the state bodies and on the part of persons entitled to the return of expropriated real estate, who are obliged to return the valorised compensation as part of their settlements. The subject of this study was exclusively the methodology and mechanism for adjusting the amounts of compensation for expropriated property, without taking into account the assessment of its objectivity when using consumer price indices instead of target indicators, but in the vast majority of unannounced indices of changes in property prices, that would most accurately reflect changes in property prices on the market. An implication of de lege ferenda demands unification and clarification of the formula of the correct mechanism for making indexing amounts of established and unpaid compensation for expropriated real estate so that an unambiguous verification of the correctness of the final result can be made.